Triad of cheiloscopy, Dactyloscopy and blood grouping-A Correlation study - Devaki, Talluri (International dental journal, 2024)
To elucidate any unique combination if any exists between Blood group, cheiloscopy, and Dactyloscopy, that might help in the identification of an individual. A total of 70 subjects of age 20-24 years were examined in the present study. Among those 60 we're female, and 10 we're males. All the subjects lip prints, left thumb print, ABO blood grouping was recorded. Among the subjects 85.7℅constituted female subjects, and 14.2℅ constituted male subjects. Left thumb print was recorded, among these 42.8℅ constituted arch type, type1 lip print was observed in 64. 5℅ subjects, among males O+ve blood group was 63 ℅, and among female subjects B+ve was the common blood group and constituted 59℅.correlation between three parameters was done by Pearson correlation statical analysis. The triad to be elucidated through the present research to aid in Forensic identification. It also substantiates the facts, where there is little evidence.